A new understanding on the electrochemical coloration mechanism of titanium surface - Tengfei Yu; Yanpeng Xue; Man Zheng; Benli Luan (Journal of Materials Research and Technology)
Electrochemical coloration technology has been extensively studied for many years due to its effectiveness in enhancing the aesthetics, corrosion resistance, and biocompatibility of Ti materials. However, the underlying coloration mechanism has not been systematically investigated and verified. Our new finding based on spectrophotometer characterization reveals that the color of oxide film is determined by the diffuse reflection light. The coloration mechanism, attributed to the selective absorption of visible light by the TiOx semiconductor film, is therefore proposed and confirmed. This absorption originates from electron transitions from the impurity levels to the conduction band. Oxide films of various colors exhibit particular absorption peaks, along with specific flat band potentials and charge carrier densities. The energy differences between the conduction band minimum and the Fermi level (EC-EF) of oxide films with orange, red, blue, and green colors are 1.77 eV, 1.50 eV, 1.25 eV, and 0.76 eV, respectively, corresponding to the redshift of their visible light absorption peaks. This new discovery provides a new understanding of Ti coloration mechanism and promotes the development of related processes and potential applications.